The Wolfpen Notebooks : A Record of Appalachian Life - Still, James, 1906-2001 (Book collections on Project MUSE., 1991)
After keeping school for six years at the forks of Troublesome Creek in the Kentucky hills, James Still moved to a century-old log house between the waters of Wolfpen Creek and Dead Mare Branch, on Little Carr Creek, and became ""the man in the bushes"" to his curious neighbors. Still joined the life of the scattered community. He raised his own food, preserved fruits and vegetables for the winter, and kept two stands of bees for honey. A neighbor remarked of Still, ""He's left a good job, and come over in here and sot down."" Still did sit down and write -- the classic novel River o